Estudio microbiológico de líquido biliar en pacientes con patología vesicular en el Hospital Básico Huaquillas. - Álvarez Pasaca, Richard Paul (2017)
The inadequate use of antibiotics has been a subject of great controversy for the complications that the misuse of these produces, many of the times this misuse is due to empirical practices by the society and of the medical professionals, new investigations have shown us the Increased bacterial resistance indexes to the first line drugs used from previous years, most of the time one of the most important factors for the poor treatment of an infectious disease is the lack of knowledge of the causal agent, which is the fundamental basis for the Treatment of the same, which was the reason for which this descriptive-transverse type study was carried out, in which the main objective was to determine the microbiological agents present in the biliary fluid in patients with vesicular pathology, the specific objectives were: 1. Establish which Are the main bacterial agents present in the biliary fluid, 2. Determine the antibiotic to which the germs found in the biliary fluid are most sensitive, 3. Carry out a therapeutic scheme aimed at a better antibiotic treatment in post-cholecystectomy patients based on the Results obtained in this research. During the research period, 50 samples (cultures and antibiograms) were carried out, which met the inclusion and exclusion criteria. As a result, 92% of the cultures were negative, the remaining 8% were positive with bacterial growth ( Gram-negative bacteria), mainly enterobacteria and Escherichia coli, were also found to be more sensitive to fluoroquinolones (ciprofloxacin, levofloxacin) and cephalosporins (cefuroxime, ceftriaxone) and that first-line drugs for antibiotic therapy used in infections in pathologies Vesicles such as first-generation cephalosporins (cephalexin) and aminopenicillins (ampicillin sulbactam, amoxicillin) had lower sensitivity and in some cases had resistance. Key words: Vesicular Pathology, Microbiological Agents, Bile liquid.